2022
DOI: 10.3390/microorganisms10040753
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Cell Factories for Efficient and Sustainable Production of Proteins and Peptides

Abstract: Filamentous fungi are a large and diverse taxonomically group of microorganisms found in all habitats worldwide. They grow as a network of cells called hyphae. Since filamentous fungi live in very diverse habitats, they produce different enzymes to degrade material for their living, for example hydrolytic enzymes to degrade various kinds of biomasses. Moreover, they produce defense proteins (antimicrobial peptides) and proteins for attaching surfaces (hydrophobins). Many of them are easy to cultivate in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 176 publications
0
40
0
2
Order By: Relevance
“…Filamentous fungi rely on external carbon sources because they are heterotrophic, but many can absorb inorganic nitrogen and other nutrients for growth and metabolism. They can make all the necessary amino acids from inorganic nitrogen [29]. Many protoplast isolation studies indicated that 0.6 M KCl acts as the best osmotic stabilizer [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Filamentous fungi rely on external carbon sources because they are heterotrophic, but many can absorb inorganic nitrogen and other nutrients for growth and metabolism. They can make all the necessary amino acids from inorganic nitrogen [29]. Many protoplast isolation studies indicated that 0.6 M KCl acts as the best osmotic stabilizer [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Mycoprotein Quorn contains protein (45%), fiber (25%), fat (13%) and carbohydrates (10%) in 100 grams of dry weight [15]. Numerous fungi that could produce mycoproteins include Rhizopus oligosporus, Aspergillus niger, and Neurospora sitophila [16]. Yeasts Saccharomyces cerevisiae and Kluyveromyces marxianus are capable of producing SCP [17].…”
Section: Corynobacterium Ammoniagenesmentioning
confidence: 99%
“…Fungi need organic matter as the primary source of carbon for energy production. There are at least eight macronutrients that need to be met: carbon, oxygen, hydrogen, nitrogen, phosphorus, potassium, sulfur, and magnesium, and there are five micronutrients: manganese, iron, zinc, copper, and molybdenum [16]. Organic carbon sources are sugars, such as glucose, fructose, and sucrose.…”
Section: Fermentation Processmentioning
confidence: 99%
“…Extracellularly secreted enzymes are more convenient for subsequent enzyme separation and extraction than intracellularly produced enzymes. In addition, the cellulase produced by fungi has a more reasonable structure, and the decomposition efficiency of the enzyme is higher [ 7 ].…”
Section: Introductionmentioning
confidence: 99%